Chemical Vapor Detection Using a Reconstituted Insect Olfactory Receptor Complex1. (28th July 2014) - Sato, Koji; Takeuchi, Shoji
Abstract The sensing of vapor odorants is highly demanded in the field of life and medical sciences. Although olfactory receptors (ORs) have potentials to recognize volatile organic compounds, the interaction of ORs, chemical vapors, and peptide components in olfactory mucus has yet to be analyzed to develop OR‐based sensors. A bioinspired electrophysiology technique is shown to record the response of reconstituted insect ORs to chemical vapors. To mimic the interface between ORs and olfactory mucus, OR expressing spheroids were loaded into a hydrogel microchamber array. A negative extracellular field potential shift of spheroids was successfully observed by the stimulation of their vapor cognate ligand. Importantly, the ligand repertoire of the OR of malaria vector mosquito examined by this method differed from that of in vivo studies. Our method is useful to develop protein‐based gas sensing techniques and to examine the binding of ORs and chemical vapors.